Phosphate and Kidney Healthy Aging - Isabel Rubio-Aliaga (Karger Publishers, 2020)
Background: The aging population is increasing rapidly, much faster than our understanding on how to promote healthy aging free of multimorbidities. The aging kidney shows a decline in its function. Whether this decline is preventable or physiological is still debated. Main risks factors for developing CKD are aging common comorbidites, such as hypertension, diabetes, and obesity. Phosphate is vital for our organism, but it is also present in a great variety of food products as food additive and preservative. Due to the higher consumption of processed food in the last century, concern has arisen if a chronic high consumption of phosphate may be toxic impacting on healthy aging. Summary: Several studies show an association between higher serum phosphate levels and a higher risk of overall mortality and cardiovascular disease. Moreover, higher phosphate levels also worsen CKD progression and may contribute to renal dysfunction in healthy individuals. Acute high phosphate intake is rare but can cause acute kidney injury. Yet, the question if controlling phosphate intake may modulate serum phosphate concentrations remains unanswered, as assessment of phosphate intake is still a difficult task. Phosphate consumption estimations by dietary recalls are largely underestimated, especially in populations groups consuming high amount of processed food. Key Message: A healthy diet with phosphate source from food may contribute to promote healthy aging and longevity.